NRJ Media as the Gold-Standard Arcobacter-Specific Detection System: Applications in Poultry Testing - Nguyen, Paul T.; Tuz, Karina; Restaino, Lawrence; Juárez, Oscar (Frontiers in Microbiology, 2022)
Arcobacter species are ubiquitous emerging pathogens with an impact that has been underestimated due to limitations in isolation and detection methods. Our group recently developed the novel NRJ Arcobacter-detection system, with major improvements in specificity and selectivity compared to other culture-based methods. In this work, the NRJ detection system was evaluated using retail whole broiler chicken carcass. Nanopore 16S rRNA gene amplicon sequencing demonstrated that Arcobacter species are found in very low abundance in retail chicken and that indigenous microbiota could be a major factor interfering with detection. Comparison of the microbiome obtained from modified Houf broth (HB) method, as the standard detection system, and the novel NRJ method, showed Arcobacter abundances of <15% and >97%, respectively. The NRJ system significantly inhibits the growth of non-target microbiota, and specifically allows the multiplication of Arcobacter species. In this report, we describe the gold-standard of Arcobacter-specific culture-based method to test food matrices, which can be used for other applications, such as clinical and environmental sampling.